Next-Generation Sequencing of Chinese Children with Congenital Hearing Loss Reveals Rare and Novel Variants in Known and Candidate Genes - Yuan Jin; Xiaozhou Liu; Qiong Zhang; Ying Xiong; Yao Hu; Haixia He; Wei Chen; Yu Sun (Biomedicines)
Background: Hearing loss (HL) is the most common disorder in newborns with a highly heterogeneous genetic background. Despite significant progress in screening and identifying genes related to congenital hearing loss, there are still candidate genes implicated in HL that remain undiscovered. Methods: We investigated HL in 43 Chinese families by segregating bilateral sensorineural HL via whole-exome sequencing (WES) and Sanger sequencing. Results: Variants were found in 10 known non-syndromic hearing loss (NSHL) genes, 5 known syndromic hearing loss (SHL) genes, and 1 candidate HL gene, ATP7B. RNA sequencing revealed ATP7B mRNA expression in developing and adult cochleae. The immunohistochemistry of the adult mouse cochlear tissue revealed the prominent expression of ATP7B in the organ of Corti and the spiral ganglion neuron. Overall, we propose a new candidate gene, ATP7B, for congenital hearing loss and novel variants in known HL genes, which expands our understanding of the etiology of HL. Conclusions: The next-generation sequencing could effectively improve the etiological diagnosis rate of congenital hearing loss in children.